A Year-Long Caregiver Training Program to Improve Neurocognition in Preschool Ugandan HIV-Exposed Children - Boivin, Michael J.; Bangirana, Paul; Nakasujja, Noeline; Page, Connie F.; Shohet, Cilly; Givon, Deborah; Bass, Judith K.; Opoka, Robert O.; Klein, Pnina S. (Journal of developmental and behavioral pediatrics, 2013)
Mediational intervention for sensitizing caregivers (MISC) is a structured program enabling caregivers to enhance their child’s cognitive and emotional development through daily interactions. The principal aim was to evaluate if a year-long MISC caregiver training program produced greater improvement in child cognitive and emotional development compared with a control program. 119 uninfected HIV-exposed preschool children and their caregivers were randomly assigned to one of two treatment arms: biweekly MISC training alternating between home and clinic for one year or a health and nutrition curriculum. All children were evaluated at baseline, 6 months, and 1 year with the Mullen Early Learning Scales, Color-Object Association Test (COAT) for memory, and Achenbach Child Behavior Checklist (CBCL) for psychiatric symptoms. Caregivers were evaluated on the same schedule with the Hopkins Symptoms Checklist (HSCL-25) for depression and anxiety.The treatment arms were compared using repeated-measures ANCOVA with child age, gender, weight, SES, caregiving quality, caregiver anxiety, and caregiver education as covariates. The MISC children had significantly greater gains compared to controls on the Mullen Receptive and Expressive Language development, and on the Mullen composite score of cognitive ability. COAT total memory for MISC children was marginally better than controls. No CBCL differences between the groups were noted. Caldwell HOME scores and observed mediational interaction scores from videotapes measuring caregiving quality also improved significantly more for the MISC group.MISC enhanced cognitive performance, especially in language development. These benefits were possibly mediated by improved caregiving and positive emotional benefit to the caregiver.
Keywords: child development, HIV, caregiver, training, Uganda, language, cognition, nutrition